The biological and clinical impact of deletions before and after large chromosomal gains in multiple myeloma - Cirrincione, Anthony; Poos, Alexandra; Ziccheddu, Bachisio; Kaddoura, Marcella; Bärtsch, Marc-Andrea; Maclachlan, Kylee; Chojnacka, Monika; Diamond, Benjamin; John, Lukas; Reichert, Philipp; Huhn, Stefanie; Blaney, Patrick; et al. (Blood, 2024)
Acquisition of a hyperdiploid (HY) karyotype or immunoglobulin heavy chain (IgH) translocations are considered key initiating events in multiple myeloma (MM). To explore if other genomic events can precede these events, we analyzed whole-genome sequencing data from 1173 MM samples. By integrating molecular time and structural variants within early chromosomal duplications, we indeed identified pregain deletions in 9.4% of patients with an HY karyotype without IgH translocations, challenging acquisition of an HY karyotype as the earliest somatic event. Remarkably, these deletions affected tumor suppressor genes (TSGs) and/or oncogenes in 2.4% of patients with an HY karyotype without IgH translocations, supporting their role in MM pathogenesis. Furthermore, our study points to postgain deletions as novel driver mechanisms in MM. Using multiomics approaches to investigate their biologic impact, we found associations with poor clinical outcome in newly diagnosed patients and profound effects on both the oncogene and TSG activity despite the diploid gene status. Overall, this study provides novel insights into the temporal dynamics of genomic alterations in MM.
Gesehen am 06.11.2024